STRATEGI BADAN PENGAWAS PEMILIHAN UMUM KABUPATEN PELALAWAN DALAM MENGAWASI PEMILIHAN KEPALA DAERAH 2020 - Firnanda Firnanda; Zaili Rusli (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
The Election Supervisory Body is one of the institutions in charge of the General Election or Pilkada which is tasked with supervising all stages of Pilkada activities with the aim of preventing and taking action against violations in the process of Pilkada stages. In the implementation, the Pelalawan Regency Bawaslu is tasked with overseeing the continuation of the 2020 Simultaneous Regional Elections in the midst of the Covid-19 Non-Natural Disaster. This study intends to find out how the Pelalawan Regency Bawaslu Supervision in the 2020 Simultaneous Regional Elections during the Covid-19 Pandemic that hit the entire territory of the Republic of Indonesia. The research method used in this study is a qualitative method with data collection techniques, data analysis, data reduction and drawing conclusions from existing data. The results of this study indicate that the supervision of Bawaslu in the simultaneous elections of Pelalawan Regency in 2020 during the Covid-19 Pandemic has been jammed as mandated by the existing regulations, namely Perbawaslu No. The findings of violations contained in the articles of Perbawaslu No. 4 of 2020. Thus, this study can conclude that the supervision carried out by the Bawaslu of Pelalawan Regency has been carried out to the maximum considering that existing violations have been given action in accordance with existing regulations.